2023
DOI: 10.1117/1.nph.11.3.033403
|View full text |Cite
|
Sign up to set email alerts
|

Linking brain activity across scales with simultaneous opto- and electrophysiology

Christopher M. Lewis,
Adrian Hoffmann,
Fritjof Helmchen

Abstract: The brain enables adaptive behavior via the dynamic coordination of diverse neuronal signals across spatial and temporal scales: from fast action potential patterns in microcircuits to slower patterns of distributed activity in brain-wide networks. Understanding principles of multiscale dynamics requires simultaneous monitoring of signals in multiple, distributed network nodes. Combining optical and electrical recordings of brain activity is promising for collecting data across multiple scales and can reveal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 223 publications
0
2
0
Order By: Relevance
“…Noise artifacts from laser scanning were minimal when imaging GCaMP6s, and were easily filtered out with a recursive notch filter 35 (Figure S1D-E). While alternative techniques can be used to further reduce noise artifacts, such as using red-shifted GCaMP sensors, or enhancing the electrode transparency with graphene 29,36 ; nanomesh arrays 37 , or other novel materials [38][39][40] , our recordings revealed that nanoporous gold was sufficient for near artifact-free imaging while allowing for dense patterning. This platform allowed us to record from hundreds of L2/3 cells in the field of view (FOV) with clearly detectable touch-evoked LFP (Figure 1E, Figure S1F-G).…”
Section: Neurogrids For Mapping Traveling Wave Dynamics During Two-ph...mentioning
confidence: 99%
“…Noise artifacts from laser scanning were minimal when imaging GCaMP6s, and were easily filtered out with a recursive notch filter 35 (Figure S1D-E). While alternative techniques can be used to further reduce noise artifacts, such as using red-shifted GCaMP sensors, or enhancing the electrode transparency with graphene 29,36 ; nanomesh arrays 37 , or other novel materials [38][39][40] , our recordings revealed that nanoporous gold was sufficient for near artifact-free imaging while allowing for dense patterning. This platform allowed us to record from hundreds of L2/3 cells in the field of view (FOV) with clearly detectable touch-evoked LFP (Figure 1E, Figure S1F-G).…”
Section: Neurogrids For Mapping Traveling Wave Dynamics During Two-ph...mentioning
confidence: 99%
“…In recent years, diverse strategies have been developed to merge in vivo neurophotonics with in vivo neuroelectronics, including transparent surface electrode arrays and penetrating electrode shanks with integrated light sources, light guides, and photodetectors. 76 84 For optical modalities that interface with brain tissue through large numerical aperture objectives that have a wide footprint and working distance of a few millimeters, unobstructed access to the surface is necessary. One such modality is 2-photon microscopy.…”
Section: In Vivo Imaging Of Rodent Cerebral Cortexmentioning
confidence: 99%